Estimates of genetic parameters for growth traits in Suffolk sheep in Brazil - Pires, M. P.; Farah, M. M. [UNESP]; Carreno, L. O. D. [UNESP]; Utsunomiya, A. T. H. [UNESP]; Ono, R. K. [UNESP]; Bertipaglia, T. S. [UNESP]; Fonseca, R. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2015)
The aim of this study was to estimate genetic parameters for growth of Suffolk, in order to provide a basis for the definition of selection strategies for breeding programs. The data analyzed are for Suffolk sheep, collected between years 2007 to 2009, from a property located in the State of Sao Paulo - Brazil, a participant in the Ovigol breeding program conducted by the company (Aries Reproduction and Breeding Sheep Ltd.) in partnership with (AbacusBio) New Zealand Limited. The evaluated characteristics were: birth weight (PN), weight gain pre-weaning (GPP) and weaning weight (PD), with registration number 1039, 636 and 649 respectively. For statistical analysis we used the GLM procedure of SAS software, for the consistency of pedigree and genetic parameter estimates software Relax2: pedigree analysis program and WOMBAT, respectively, were used. The general linear model included sex, contemporary group (type of birth and year of birth), covariate age at weaning (GPP and PD) with a quadratic effect, direct genetic effect, maternal permanent environmental effect and residual effect. Heritability estimates for PN, PD and GPP were 0.06, 0.42 and 0.37, respectively. Genetic correlations between PN and GPP, and PN and PD and GPP were -0.10, -0.03 and 0.97, respectively. In the study population characteristics GPP and PD have a high response to selection, unlike the PN. The GPP and PN characteristics are enough to make a selection index, it is advisable to monitor the PN in the initial phase of the program.
Keywords: heritability; animal breeding; sheep industry; genetic